2008
DOI: 10.1021/ic800838b
|View full text |Cite
|
Sign up to set email alerts
|

The Boron Connection: A Parallel Description of Aromatic, Bonding, and Structural Characteristics of Hydrogenated Silicon−Carbon Clusters and Isovalent Carboranes

Abstract: The aromatic, bonding, and structural characteristics of the Si 4C 2H 2-C 2B 4H 6, Si 2C 4H 4-C 4B 2H 6, and other Si n C 2H 2-C 2B n H n+2 ( n = 1, 2, 3, 5) isovalent pairs are studied using density functional theory (DFT) and coupled cluster methods to fully illustrate the homology of the two species. This homology, which is based on the replacement of the carborane B-H units by isovalent Si atoms, is extended to all three characteristics (structural, electronic, and aromatic) and includes all three lowest-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…6 It is known for more than 30 years that chemical analo-gies, such as the isolobal analogy introduced through the pioneering work of Hoffman, 11 allow the correlation of seemingly very different chemical species, such as organic hydrocarbon fragments with transition metal ligands. [18][19][20] Boranes and carboranes constitute a very rich and well established branch of chemistry [12][13][14][15][16][17] with well known structural and stability rules [12][13][14][15] and powerful concepts. Thus, as Hoffman explains in his Nobel lecture, 11 any hydrocarbon may be constructed on paper from methyl groups, methylenes, methynes, and carbon atoms by substitution and introduction of heteroatoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It is known for more than 30 years that chemical analo-gies, such as the isolobal analogy introduced through the pioneering work of Hoffman, 11 allow the correlation of seemingly very different chemical species, such as organic hydrocarbon fragments with transition metal ligands. [18][19][20] Boranes and carboranes constitute a very rich and well established branch of chemistry [12][13][14][15][16][17] with well known structural and stability rules [12][13][14][15] and powerful concepts. Thus, as Hoffman explains in his Nobel lecture, 11 any hydrocarbon may be constructed on paper from methyl groups, methylenes, methynes, and carbon atoms by substitution and introduction of heteroatoms.…”
Section: Introductionmentioning
confidence: 99%
“…This way all of the skeletons and functional groupings imaginable, from ethane to tetrodotoxin, may be obtained. [18][19][20] The idea of connecting the structural Chemistry of B n H n and Si n clusters is not totally new but it goes back to Mingos and co-workers 22 and Wales 23 ͑in a rather different context͒. CH, Co͑CO͒ 3 and CH 3 , Mn͑CO͒ 5 can be considered as classical examples of isolobal fragments.…”
Section: Introductionmentioning
confidence: 99%
“…The BH→Si boron connection has originated from the fluxionality and similarity of magic silicon clusters (and, in particular, of the controversial Si 6 cluster [11-13]) with the corresponding deltahedral boranes. It was shown initially [11,12] that the Si 6 2- dianion and the corresponding isovalent B 6 H 6 2- borane have exactly the same geometrical and electronic structure (including the frontier orbitals) as shown in Figure 3 and they are, therefore, isolobal and homologous.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently similar results should be able to be obtained for germanium-based multidecker sandwiches, since Si and Ge structures are fully homologous and isolobal and the Si→Ge substitution rule is valid almost everywhere. This is equivalent to the BH→Ge substitution, which seems to be more valid compared to the BH→Si substitution, in particular for larger clusters [12,13]. This is related to the fact that the BH→Si (1) is based on the much stronger BH 2- →Si 2- substitution between dianions [10,11] from which the equivalence Si n-2 C 2 H 2 ⇔C 2 B n-2 H n is obtained by the well-tested substitutions Si1 - →CH and BH 1- →CH, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[20]) even today, and so is the Si/Bi interface, which leads us to the core/shell Si/Bi nanocrystalline structures. As a zero th order-zero th size 'bottom up' approach to this subject can be considered the recent study of binary of Si/Bi clusters by the present author [26,27], which has revealed many interesting effects on these clusters such as fluxional behavior, similar to organometallic carboranes [28][29][30][31][32] and 'structural reciprocity' [27] with respect to the Bi ? Si substitution.…”
Section: Introductionmentioning
confidence: 99%